Castle diary: the journal of Tobias Burgess, page - Platt, Richard; Riddell, Chris (Walker London, 2003)
As a page in his uncle's castle in thirteenth-century England, eleven-year-old Tobias records in his journal his experiences learning how to hunt, play games of skill, and behave in noble society. Includes notes on noblemen, castles, and feudalism. Suggested level: primary, intermediate